Representações de estudantes sobre seus pares com deficiência física na escola comum : um estudo a partir da teoria dos modelos organizadores do pensamento - Magnabosco, Molise de Bem (2014)
The paradigm of inclusive education, established as public policy in Brazil since the 90s, demands overcoming discriminatory practices from the proposal for an education that recognizes and values the diversity present in society. With its implementation, the school has welcomed students who thitherto remained outside the educational system, such as people with disabilities. The inclusion of these students in the ordinary teaching has been related to many benefits both for these guys and for those who do not have disabilities. There are thus a large number of studies that focus on school inclusion, but few propose to know what children think about it. From this, we outline the purpose of this research: to identify the representations that students without disabilities elaborate on children with disabilities before the establishment of interpersonal relationships in everyday school life. Such representations were analyzed from the Theory of Organizing Models of Thought, as well as commenting on their relation with prejudice were made. The study included 60 children, with ages between 6 and 8 years old, studying in 1st cycle of Basic Education schools of Municipal School of Rondonópolis. These children were interviewed individually by the application of an instrument illustrating a conflict between two children in wich one of them had disabilities. Given this circumstance, students were asked to report the thoughts and feelings of the characters represented, as well as to indicate one of them as their choice for situations of interpersonal relationships (make friends, play and share school activities). The results showed the prevalence of the medical model in the representation of disability as well as the action of prejudice and stigma. Thus, the representations were centered on the limitations of the subject resulting from the disability and the attribution to him of negative feelings. Altruism and the need to overcome the disability to conquer happiness were other elements that detached and also strengthen the understanding of the disability by the pathology bias. From these results, there is a need to develop actions that promote inclusion comprehension grounded in a social perspective.